If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + 2(4y + 3) = 0 Reorder the terms: 10 + 2(3 + 4y) = 0 10 + (3 * 2 + 4y * 2) = 0 10 + (6 + 8y) = 0 Combine like terms: 10 + 6 = 16 16 + 8y = 0 Solving 16 + 8y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-16' to each side of the equation. 16 + -16 + 8y = 0 + -16 Combine like terms: 16 + -16 = 0 0 + 8y = 0 + -16 8y = 0 + -16 Combine like terms: 0 + -16 = -16 8y = -16 Divide each side by '8'. y = -2 Simplifying y = -2
| 3x-2(12-x)=4(2x-3)+3(x+1) | | 6-5c=-14 | | 6(1-x)+4=3(2-x)-4 | | 4x+10=90-6 | | 40-2(x+1)=90 | | 4k+6=6k-2 | | 6(2x+1)+7=9x+1 | | 6x+9=-119-10x | | 3(7x-1)+8(3-2x)=1 | | -2*5= | | 5(2x+3)-3(x+1)=5 | | 8(x-2)-2(2x-1)=2x+1 | | -2(5r+3)= | | 5a+30b=25 | | 5(3x-4)=8x+1 | | 6a-4=8 | | 3(10a)= | | 2x-3(2-x)=4 | | 4(x+3)-2=2 | | 3(x+1)+2(2x+7)=3 | | 5(f-12)=9+5f | | 6x+y-8x+y= | | 3(2x+5)+5(x-1)=-1 | | 7(x-1)-2(x-2)=3 | | 2(3x+8)-3(x-2)=25 | | 6x-5(4x+13)=33 | | 11x-1=3(3x-5) | | 7(3-x)+9x=26 | | 8(3x+2)=4(5x+1) | | 2(4x-5)= | | 7x+6=2(3x+2) | | 4(5x-1)=3(4x+12) |